Presenting Cebuano cinema at the MEMORY! International Film Heritage Festival - Grant, Paul Douglas (Plaridel, 2018)
Access online through this link: https://www.plarideljournal.org/article/presenting-cebuano-cinema-at-the-memory-international-film-heritage-festival